Struggle and Solidarity Seven Stories of How Americans Fought for Their Mental Health Through Federal Legislation. - Compton, Michael T. (American Psychiatric Association Publishing, 2022)
This book presents seven key pieces of federal legislation and demonstrates how public policies-even when not explicitly mental health-related-can shape social determinants and improve mental health.